Imperial coinage and representation of Iulia Cornelia Salonina (253-268 AD) - Adrián Gordón Zan (Lucentum)
We have little information about Iulia Cornelia Salonina because of the scant attention she received from classical authors, among whom Aurelius Victor, Zonaras, and the Historia Augusta mention her. However, we know that she was the wife of Gallienus, who ruled between 253 and 268, and that is why we have her presence in numismatic and epigraphic sources. Considering the importance of coinage as a medium for the distribution of the imperial image, this study presents the main characteristics of the typology of the imperial coinage of Salonina. To carry it out, approximately 105,000 coins from the domus Licinia Augusta present in 121 coin hoards of the Roman Empire have been analysed, following the methodology of researchers such as Duncan-Jones, Noreña, and Rowan. The content is divided into an introduction; a section that collects the information that we can obtain of Salonina through literary sources and epigraphy, as well as the current literature in this regard; a main section that includes the study of its coinage; and finally, the conclusions. As a result, we determine that there are clear differences between the periods 253-259 and 260-268, where she was more associated with traditional divinities in the first case and with messages linked to the imperial family, her virtues, and the divinities in the second. Also, this analysis allows us to reconsider some of the statements made by Cesano, De Blois, Ferrari, or Geiger to advance our knowledge of the imperial representation of this Augusta.